2007
DOI: 10.3748/wjg.v13.i20.2855
|View full text |Cite
|
Sign up to set email alerts
|

New concept of ileocecal junction: Intussusception of the terminal ileum into the cecum

Abstract: AIM:To prove that the terminal ileum is intussuscepted into the cecum creating the ileocecal junction, contrary to previous valvular concept which has been widely believed. METHODS:This study is based on gross and microscopic examinations of fresh specimens derived from colonic operations (right hemicolectomy or subtotal colectomy). Data compiled from observing and dissecting of specimens of seven patients are used to examine both gross and microscopic appearance of ileocecal junction. RESULTS:Intussusception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
1
2
1
Order By: Relevance
“…The most predominantly seen morphological type of ICV in our study was type II C, followed by classical and the least common types of ICV were type IVA, IVB, and V. This finding of the present study was like the findings of Kellogg (1914) and Short A (1919), who found that the most common type of ICV was valvular with variations followed by papillary and lipomatous [ 8 , 17 ]. Conversely, our findings contradict the findings of Buirge (1943) and Awapittaya (2007) who observed that the most common morphological type of ICV was type I, and type IIC was the least common type [ 16 , 18 ]. In all three cases of fetal autopsy studied, ICJ had reverse-S morphology and the most common morphological type of ICV was papillary type.…”
Section: Discussioncontrasting
confidence: 99%
“…The most predominantly seen morphological type of ICV in our study was type II C, followed by classical and the least common types of ICV were type IVA, IVB, and V. This finding of the present study was like the findings of Kellogg (1914) and Short A (1919), who found that the most common type of ICV was valvular with variations followed by papillary and lipomatous [ 8 , 17 ]. Conversely, our findings contradict the findings of Buirge (1943) and Awapittaya (2007) who observed that the most common morphological type of ICV was type I, and type IIC was the least common type [ 16 , 18 ]. In all three cases of fetal autopsy studied, ICJ had reverse-S morphology and the most common morphological type of ICV was papillary type.…”
Section: Discussioncontrasting
confidence: 99%
“…The anatomy and neuroanatomy of the ileocecal junction showed in our study suggest that the ileocecal junction is a simple intussusception of the ileum into the cecum, which is in accordance with the latest concept of the ICV: intussusception of the terminal ileum into the cecum (Awapittaya et al, 2007). The designs of previous techniques suggested for ICV replacement are not close to the original layout of the normal ileocecal junction (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Although Awapittaya et al (2007) have concluded that the ileocaecal valve is a simple intussusception of the terminal ileum into the caecum on the basis of its gross anatomy and the microscopic observations of human specimens, the structural characteristics of the ileocaecal junction remain obscure. These include the organization of muscle bundles in the terminal ileum, their continuity with those of the ileum or caecum, the characteristics of the intrinsic nerve plexus, the presence or absence of the interstitial cells of Cajal (ICC) and the existence of any specialized structures forming the valve.…”
Section: Introductionmentioning
confidence: 99%